Proposta metodológica simplificada para a análise do Cadastro Ambiental Rural – CAR: um estudo de caso no município de Monte Alegre-PA - ALMEIDA, Márcia de (2023)
It is expressive in the state of Pará the amount of Rural Environmental Registers – CAR awaiting analysis by the competent environmental agency. In this regard, the present study aimed to propose a simplified methodology for the analysis of CAR that contemplates the different Brazilian typologies. With the help of the free software QGIS, the digital processing of the data was carried out, using the tool reclassify by table and the complement SemiAutomatic Classification Plugin - SCP for the transitions and reclassifications of the classes of the mapbiomes collection 6.0 (2002-2020). The results of applying the methodology showed the peculiarities of the spatial distribution of the municipality of Monte Alegre, highlighting the areas of Remnant Native Vegetation, with differentiation between the typologies of existing biomes, Consolidated Areas, Anthropized Areas, Water Mass and Regeneration, with views of the CAR categories. Therefore, the mapping of land cover was carried out effectively and could contribute to the fluidity of the process of registration and analysis of the CAR, presenting important contributions to studies of environmental regularization of rural properties.